Acquired resistance mechanisms to afatinib in HER2‐amplified gastric cancer cells. Issue 8 (24th June 2019) - Yoshioka, Takahiro; Shien, Kazuhiko; Takeda, Tatsuaki; Takahashi, Yuta; Kurihara, Eisuke; Ogoshi, Yusuke; Namba, Kei; Torigoe, Hidejiro; Sato, Hiroki; Tomida, Shuta; Yamamoto, Hiromasa; Soh, Junichi; et al.
Abstract: Cancer treatment, especially that for breast and lung cancer, has entered a new era and continues to evolve, with the development of genome analysis technology and the advent of molecular targeted drugs including tyrosine kinase inhibitors. Nevertheless, acquired drug resistance to molecular targeted drugs is unavoidable, creating a clinically challenging problem. We recently reported the antitumor effect of a pan‐HER inhibitor, afatinib, against human epidermal growth factor receptor 2 ( HER2 )‐amplified gastric cancer cells. The purpose of the present study was to identify the mechanisms of acquired afatinib resistance and to investigate the treatment strategies for HER2 ‐amplified gastric cancer cells. Two afatinib‐resistant gastric cancer cell lines were established from 2 HER2 ‐amplified cell lines, N87 and SNU216. Subsequently, we investigated the molecular profiles of resistant cells. The activation of the HER2 pathway was downregulated in N87‐derived resistant cells, whereas it was upregulated in SNU216‐derived resistant cells. In the N87‐derived cell line, both MET and AXL were activated, and combination treatment with afatinib and cabozantinib, a multikinase inhibitor that inhibits MET and AXL, suppressed the cell growth of cells with acquired resistance both in vitro and in vivo. In the SNU216‐derived cell line, YES1, which is a member of the Src family, was remarkably activated, and dasatinib, a Src inhibitor, exerted a strong antitumor effect in these cells. In conclusion, we identified MET and AXL activation in addition to YES1 activation as novel mechanisms of afatinib resistance in HER2‐driven gastric cancer. Our results also indicated that treatment strategies targeting individual mechanisms of resistance are key to overcoming such resistance. Abstract : The purpose of this study was to identify the mechanisms of acquired afatinib resistance and to investigate the treatment strategies for HER2‐amplified gastric cancer cells. We identified MET and AXL activation in addition to YES1 activation as novel mechanisms of afatinib resistance in HER2‐driven gastric cancer. Treatment strategies targeting individual mechanisms of resistance are key to overcoming such resistance.